Role of cell deformability in the two-dimensional melting of biological tissues - Li, Yan-Wei (2019)
The size and shape of a large variety of polymeric particles, including biological cells, star polymers, dendrimes, and microgels, depend on the applied stresses as the particles are extremely soft. In high-density suspensions these particles deform as stressed by their neighbors, which implies that the interparticle interaction becomes of many-body type. Investigating a two-dimensional model of cell tissue, where the single particle shear modulus is related to the cell adhesion strength, here we show that the particle deformability affects the melting scenario. On increasing the temperature, stiff particles undergo a first-order solid/liquid transition, while soft ones undergo a continuous solid/hexatic transition followed by a discontinuous hexatic/liquid transition. At zero temperature the melting transition driven by the decrease of the adhesion strength occurs through two continuous transitions as in the Kosterlitz, Thouless, Halperin, Nelson, and Young scenario. Thus, there is a range of adhesion strength values where the hexatic phase is stable at zero temperature, which suggests that the intermediate phase of the epithelial-to-mesenchymal transition could be hexatic type.